Efficient TALEN construction and evaluation methods for human cell and animal applications. (6th February 2013) - Sakuma, Tetsushi; Hosoi, Sayaka; Woltjen, Knut; Suzuki, Ken‐ichi; Kashiwagi, Keiko; Wada, Housei; Ochiai, Hiroshi; Miyamoto, Tatsuo; Kawai, Narudo; Sasakura, Yasunori; Matsuura, Shinya; Okada, Yasushi; et al.
<x xml:space="preserve">Abstract</x> Transcription activator–like effector nucleases (TALENs) have recently arisen as effective tools for targeted genome engineering. Here, we report streamlined methods for the construction and evaluation of TALENs based on the 'Golden Gate TALEN and TAL Effector Kit' (Addgene). We diminished array vector requirements and increased assembly rates using six‐module concatemerization. We altered the architecture of the native TALEN protein to increase nuclease activity and replaced the final destination vector with a mammalian expression/in vitro transcription vector bearing both CMV and T7 promoters. Using our methods, the whole process, from initiating construction to completing evaluation directly in mammalian cells, requires only 1 week. Furthermore, TALENs constructed in this manner may be directly applied to transfection of cultured cells or mRNA synthesis for use in animals and embryos. In this article, we show genomic modification of HEK293T cells, human induced pluripotent stem cells, Drosophila melanogaster, Danio rerio and Xenopus laevis, using custom‐made TALENs constructed and evaluated with our protocol. Our methods are more time efficient compared with conventional yeast‐based evaluation methods and provide a more accessible and effective protocol for the application of TALENs in various model organisms.